Hyperlocal journalism : the decline of local newspapers and the rise of online community news - Harte, David (Routledge, 2019)
"Hyperlocal Journalism critically explores the development of citizen-led community news operations that have appeared in the wake of the withdrawal of commercial journalism from local communities at the beginning of the 21st century. The book draws together a wide range of original research by way of case studies, interviews, and industry and policy analysis, to give a complete view of what is happening to communities as their local newspapers close or decline, to be replaced by emerging forms of digital news provision. This study takes the United Kingdom as its focus but its findings speak to common issues found in local media systems in Western democracies. The authors investigate who is producing hyperlocal news and why, as well as production practices, models of community and participatory journalism, and the economics of hyperlocal operations. In looking holistically at hyperlocal news, Hyperlocal Journalism paints a vivid picture of citizens creating their own news services via social media and on free blogging platforms to hold power to account, redress negative reputational geographies, and to tell everyday stories of community life. It also raises key questions about sustainability of such endeavours in the face of optimism from commentators and policy-makers"--